Trade Agreements and International Technology Transfer - Martínez Zarzoso, Inmaculada (2020)
This is the first paper that analyzes for a global sample how trade agreements that include technologyrelated provisions impact exports of goods, and how this impact differs depending on the technology content of the goods. It includes estimations of a structural gravity model for a panel of 176 countries over the period 1995-2015. The model differentiates between provisions relating technology transfer, technical cooperation, research and development (R&D), and patents and intellectual property rights. It also estimates the differences in these effects depending on whether the trade flow in question is between countries with similar or different levels of development. The main results indicate that regional trade agreements (RTAs) that contain technology provisions generate a significantly higher volume of trade than RTAs that do not, after controlling for the depth of the RTAs. For countries that ratify RTAs that include such provisions, it is exports of technology-intensive goods that increase the most. Trade agreements including such provisions have a heterogeneous effect that varies by income level of the trading partners and depends on the extent to which the RTA incorporates other provisions.